(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the performance competencies possessed by the physical education teacher from the point of view of physical education teachers, identifying the differences in the estimates of physical education teachers for the performance competencies necessary for physical education teachers due to the variable of gender and years of experience. The researcher used descriptive approach, the sample of this study consisted of (272) physical education teachers in Mafraq Governorate, the researcher used questionnaire tool, The results of the study were as follows: The performance competencies possessed by the physical education teacher from the point of view of physical education teachers were high for: the tool as a whole, the field of good planning for teaching, the field of lesson implementation, the field of Control and assessment